Preparation method of fast-charging lithium battery negative electrode material

CN117334882BActive Publication Date: 2026-10-30青岛华腾石墨科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311546649.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-20
Publication Date
2026-10-30
Estimated Expiration
2043-11-20

AI Technical Summary

Technical Problem

[0004]上述负极材料是将针状生焦经低温煅烧后与粘接剂混合造粒后再与液相包覆剂、纳米导电剂混合后碳化,低温煅烧的温度较高,均达到1000℃以上,针状生焦在高温下不断逸出挥发分,同时发生分解、缩聚反应,导致结构重排和体积收缩,使得石墨负极材料的层间距较小,真密度较高,因此不利于锂离子的扩散,锂离子的扩散速率较低,严重影响了锂离子电池的快充性能,导致锂离子电池功率性能差,大电流充电性能低,限制了锂离子电池的应用

Benefits of technology

1、本申请的方法,通过将石墨原料与氯化锡、六亚甲基四胺等组分混合后冷冻干燥,与粘结剂混合、煅烧后压制成型,经包覆后碳化,在骨料中填充锡颗粒,从而降低负极材料中石墨的层间距,增加锂离子的扩散速率,提高快速充放电效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the field of lithium battery negative electrode materials, and specifically discloses a preparation process of a fast-charging lithium battery negative electrode material, which comprises the following steps: crushing, grinding and grading graphite raw materials to obtain aggregates; dispersing tin chloride and hexamethylenetetramine in distilled water, heating to 180-200 DEG C and keeping the temperature for 10-12 hours, cooling, and preparing a blending liquid; mixing the aggregates and the blending liquid, freeze-drying, mixing with a binder, and pressing into a sheet; crushing and grading the sheet, calcining at 750-800 DEG C in nitrogen, and preparing a composite material; mixing and coating the composite material and a carbon source, granulating, and preparing a coated material; and carbonizing the coated material in an inert atmosphere, and preparing a negative electrode material. The negative electrode material prepared by the preparation method has the advantages of low specific surface area, good fast-charging performance and good cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium battery anode material technology, and more specifically, it relates to a method for preparing a fast-charging lithium battery anode material. Background Technology

[0002] Negative electrode materials for lithium-ion batteries can include graphite-based materials, non-graphite carbon materials, silicon-based materials, silicon suboxide materials, tin-based materials, and titanium-based materials. Among these, graphite has attracted widespread attention due to its abundant resources, excellent conductivity, low price, high capacity, good cycle performance, and superior rate performance, greatly increasing the research opportunities for graphite materials in electrode applications. Graphite negative electrode materials are mainly made from graphite raw materials such as petroleum coke, pitch coke, and coal tar pitch as aggregates, processed through crushing, grading, shaping, and graphitization. Graphite has a two-dimensional layered structure with an interlayer spacing of 0.335 nm, forming lithium intercalation compounds. The theoretical specific capacity reaches 370 mA·h / g, showing broad market application prospects.

[0003] In the prior art, Chinese invention patent application No. 2022107988736 discloses a method for preparing a negative electrode material, including the following steps: Step 1, crushing, grinding, and classifying needle-shaped raw coke to obtain a first aggregate; Step 2, calcining the needle-shaped raw coke at low temperature, and then crushing, grinding, and classifying it to obtain a second aggregate; Step 3, stirring the second aggregate with a binder to dynamically granulate it; Step 4, sieving the granulated product, and then mixing it with the first aggregate and graphitizing it; Step 5, fusing the graphitized product with a liquid phase coating agent and adding a nano-conductive agent; Step 6, carbonizing the fused product, and then directly sieving and demagnetizing it to obtain a composite graphite negative electrode material.

[0004] The aforementioned anode material is made by calcining needle-shaped raw coke at low temperature, mixing it with a binder to form granules, and then mixing it with a liquid-phase coating agent and a nano-conductive agent before carbonization. The low-temperature calcination temperature is relatively high, reaching over 1000℃. At high temperatures, the needle-shaped raw coke continuously releases volatiles and undergoes decomposition and condensation reactions, leading to structural rearrangement and volume shrinkage. This results in a smaller interlayer spacing and higher true density in the graphite anode material, which is not conducive to lithium-ion diffusion. The low diffusion rate of lithium ions severely affects the fast-charging performance of lithium-ion batteries, resulting in poor power performance and low high-current charging performance, thus limiting the application of lithium-ion batteries. Summary of the Invention

[0005] To improve the fast-charging performance of graphite anode materials, this application provides a method for preparing fast-charging lithium battery anode materials.

[0006] In a first aspect, this application provides a method for preparing a negative electrode material for fast-charging lithium batteries, employing the following technical solution: A method for preparing a negative electrode material for fast-charging lithium batteries includes the following steps: Graphite raw materials are crushed, ground, and graded to obtain aggregates; Sturm chloride and hexamethylenetetramine are dispersed in distilled water, heated to 180-200℃ and kept at that temperature for 10-12 hours, then cooled to obtain a blend. The aggregate and the blend liquid are freeze-dried, mixed with a binder, and pressed into a sheet to obtain a sheet material. The composite material is prepared by pulverizing and classifying the sheet material and then calcining it in nitrogen at 750-800℃. The composite material and carbon source are mixed and coated, then granulated to obtain the coated material; The coating is carbonized under an inert atmosphere to obtain the negative electrode material.

[0007] By employing the above technical solution, graphite raw materials are pulverized into aggregates, which are then mixed with a binder and a blend containing tin chloride and hexamethylenetetramine. After freeze-drying, tin chloride and hexamethylenetetramine are loaded onto the aggregates. When mixed with the binder, the pores created during freeze-drying are filled. Upon calcination, the tin oxidizes to form tin oxide. Because the aggregates contain many functional groups on their surface, they are carbonized during calcination to form a stable carbon skeleton. The tin oxide reacts with the reduced carbon during calcination, reducing the tin oxide to metallic tin particles. The carbon is distributed within the carbon framework structure. Simultaneously, some carbon is oxidized to generate carbon dioxide, which escapes from the system, causing the material to shrink in volume. This results in a composite material with a porous spherical structure. The porous structure provides a faster lithium-ion transport pathway, allowing lithium ions to be inserted and extracted onto the electrode more quickly, thus achieving faster charging and discharging speeds. Furthermore, tin particles can bind a high proportion of lithium ions, resulting in a high battery capacity. The carbon material formed by calcining the aggregate can limit the volume expansion of tin, reducing its volume change during charging and discharging and improving cycle stability.

[0008] Optionally, the amounts of each raw material used in the negative electrode material are as follows: 10-20 parts aggregate, 3-6 parts tin chloride, 2-4 parts hexamethylenetetramine, 10-15 parts distilled water, 1-2 parts binder, and 0.1-0.2 parts carbon source.

[0009] By adopting the above technical solutions, the amount of each of the above raw materials can be used to obtain nitrogen and tin-doped negative electrode materials, thereby exhibiting better battery cycle performance and rate charge / discharge performance.

[0010] Optionally, the carbon source is a modified phenolic resin, which comprises phenolic resin, nickel nitrate, and carbon nanotubes in a mass ratio of 1:0.05-0.1:0.1-0.2.

[0011] By adopting the above technical solution, nickel nitrate and carbon nanotubes are added to phenolic resin. After the carbon source is coated on the surface of the composite material and carbonized, the nickel nitrate decomposes at high temperature to generate molten NiO. The molten NiO agglomerates into NiO particles in the pores of the carbonized phenolic resin. The phenolic resin undergoes thermal decomposition at high temperature to generate carbon, which is then oxidized to carbon monoxide. The molten NiO catalyzes the carbon monoxide to achieve in-situ growth of carbon nanowires, which are then uniformly distributed in the pores of the carbonized phenolic resin. The carbon nanowires interweave with each other, covering the surface of the carbon layer and connecting with the carbonized layer between the pores of the carbonized phenolic resin, improving the structural stability of the carbon layer and supporting the carbon layer. This reduces the cycle expansion of the negative electrode material and improves the cycle performance. The carbon nanotubes act as anchors in the carbonized layer formed after the carbonization of the phenolic resin, and are distributed in an interwoven manner in the carbonized layer, providing good reinforcement to the carbonized layer. This further improves the structural stability of the carbonized layer and enhances the cycle stability of the negative electrode material.

[0012] Optionally, the modified phenolic resin is prepared as follows: carbon nanotubes and nickel nitrate are mixed evenly and then added to a 2-4 wt% aqueous solution of silane coupling agent, impregnated and dried to form a blend; Dissolve the phenolic resin in a solvent with 1.5-2 times its weight, add the blend, impregnate, dry, and pulverize.

[0013] By adopting the above technical solution, the pretreatment of carbon nanotubes and nickel nitrate with silane coupling agent can improve the dispersion uniformity of carbon nanotubes and nickel nitrate with phenolic resin, thereby making carbon nanotubes and nickel nitrate uniformly distributed in the carbonized layer formed after carbonization of phenolic resin, thus improving the strength and toughness of the carbonized layer, and thus improving the cycle stability of the anode material.

[0014] Optionally, the mass ratio of the carbon source to the composite material is 0.1-0.3:1.

[0015] By adopting the above technical solution, the carbon source and composite material are mixed and coated in the above mass ratio, which can make the carbon source uniformly coated and ensure the strength of the coating, thus greatly increasing the rate of increase while ensuring the energy density.

[0016] Optionally, the composite material and carbon source are mixed and coated at a temperature of 200-250℃, a granulation pressure of 1.3-1.7MPa, and a granulation time of 1.5-2h.

[0017] By adopting the above technical solution, the carbon source is fully softened and uniformly coated on the surface of spherical graphite at this temperature, repairing some of the defects on the surface of spherical graphite. The coating is uniform, and after granulation, a coating with a certain strength is formed.

[0018] Optionally, the graphite raw material includes 30-60 wt% of needle coke A composed of an inlaid structure and 40-70 wt% of needle coke B composed of a fibrous structure.

[0019] By adopting the above technical solutions, the graphite anode materials obtained by needle coke composed of fiber structure and needle coke composed of inlaid structure have good orientation and fast lithium ion diffusion. They can not only provide more electrochemical reaction active sites, but also shorten the diffusion path of lithium ions inside the electrode, thereby reducing charge transfer impedance and lithium ion diffusion impedance and improving its fast charging performance.

[0020] Optionally, the inert gas is argon, the carbonization temperature is 1200-1400℃, and the carbonization time is 3-10h.

[0021] By adopting the above technical solution, a uniform carbon layer is formed on the surface of the composite material through high-temperature calcination, which reduces the specific surface area of ​​the negative electrode material, increases the tap density, improves the diffusion rate of lithium ions, and improves the fast-charging performance of the negative electrode material.

[0022] Optionally, before the coating is carbonized, it undergoes the following pretreatment: manganese chloride is dissolved in ethanol to prepare a spraying solution with a concentration of 10-20 wt%, which is then uniformly sprayed onto the coating and dried. The mass ratio of the spraying solution to the coating is 0.08-0.12:1.

[0023] By adopting the above technical solution, manganese chloride is sprayed onto a coating material, which is then carbonized to form a graphite anode material. The manganese chloride is then carbonized, melted, and coated onto the graphite anode material. The manganese chloride fills the pores on the surface of the graphite anode material and forms a stable coating layer. The presence of metal ions improves the conductivity of the anode material and provides more lithium insertion sites, thereby improving the charge / discharge capacity and rate performance. During cycling, the unstable manganese chloride coating layer falls off, but as cycling progresses and the operating temperature increases, the manganese chloride coating layer becomes more stable, and the cycle performance is also higher. Therefore, the longer the cycle of the anode material, the better its cycle stability.

[0024] Optionally, the binder comprises polydopamine and molybdenum trioxide in a mass ratio of 9.6-10:1. By adopting the above technical solution, polydopamine has properties similar to mussel adhesive proteins, which can adhere aggregates and facilitate compression molding. Molybdenum trioxide is used as the molybdenum source, and molybdenum carbide is formed after carbonization. Polydopamine is used as the carbon and nitrogen source, and mesoporous carbon matrix is ​​formed after carbonization. Molybdenum carbide nanocrystals are uniformly loaded in the porous carbon layer. The nanotube structure with a large aspect ratio can shorten the migration path of lithium ions in the electrolyte and improve the charging and discharging speed. The conductive network formed by the interconnection of one-dimensional porous nanostructures can improve the migration efficiency of lithium ions and electrons. Moreover, the large specific surface area helps to provide more lithium active sites. More importantly, the mesoporous nitrogen-doped carbon nanotube framework can act as a protective layer to inhibit the aggregation of molybdenum carbide nanoparticles, alleviate volume strain, and improve the electronic conductivity of the material.

[0025] Optionally, the adhesive is made by the following method: Molybdenum trioxide was added to deionized water and sonicated until homogeneous. Oxalic acid dihydrate was added, and the temperature was raised to 80-90℃. After stirring until homogeneous, isopropanol and polydopamine were added. After sonication, the temperature was raised to 180-200℃ and reacted for 20-24 hours. The mixture was then centrifuged, vacuum dried, and ground.

[0026] By adopting the above technical solution, molybdenum trioxide and oxalic acid are mixed to form a molybdenum oxalate solution, which is then reacted with polydopamine via hydrothermal reaction to obtain a nitrogen-doped Mo-PDA nanotube precursor. After heat treatment in an inert gas atmosphere, it is carbonized to form a nitrogen-doped porous carbon layer.

[0027] In summary, this application has the following beneficial effects: 1. The method of this application involves mixing graphite raw materials with components such as tin chloride and hexamethylenetetramine, freeze-drying the mixture, mixing it with a binder, calcining it, pressing it into shape, coating it, and then carbonizing it. Tin particles are then filled into the aggregate, thereby reducing the interlayer spacing of graphite in the negative electrode material, increasing the diffusion rate of lithium ions, and improving the fast charge and discharge effect.

[0028] 2. In this application, two different needle cokes are preferably used, namely, an inlaid structure and a fiber structure. The negative electrode material made of needle cokes with different structures has good orientation and fast lithium ion diffusion speed. It can not only provide more electrochemical reaction active sites, but also shorten the diffusion path of lithium ions inside the electrode, so as to achieve fast charging effect.

[0029] 3. In this application, nickel nitrate and carbon nanotubes are preferably used to modify phenolic resin. After high-temperature carbonization, nickel nitrate forms molten NiO particles, which are uniformly distributed in the carbonized layer formed by the carbonization of phenolic resin and catalyze the in-situ growth of carbon nanowires in the carbonized layer. The carbon nanowires interlaced on the carbonized layer enhance and toughen the carbonized layer, thereby reducing the expansion of the carbonized layer and improving the cycle stability of the negative electrode material. The addition of carbon nanotubes further improves the conductivity of the negative electrode material, increases the diffusion rate of lithium ions, and improves the cycle stability of the carbonized layer.

[0030] 4. In this application, polydopamine and molybdenum trioxide are preferably used as binders. Polydopamine has the adhesiveness of mussel protein, which can achieve the bonding between aggregates. During carbonization, molybdenum trioxide is used as a molybdenum source to form molybdenum carbide, and polydopamine is used as a nitrogen and carbon source to form nitrogen-doped mesoporous nanotube materials. The internally open mesoporous nanotubes are conducive to releasing the internal stress generated by the volume expansion of the active material during cycling. Moreover, the larger specific surface area can promote the contact between the electrode material and the electrolyte, provide more lithium storage sites, and improve the migration efficiency of electrons and lithium ions. Therefore, it can improve the cycle performance and fast charging effect of the negative electrode material. Detailed Implementation

[0031] Preparation Examples of Modified Phenolic Resins 1-4 Preparation Example 1: 0.1 kg of nickel nitrate and 0.2 kg of carbon nanotubes of type L-MWNT-4060 were dispersed in 1 kg of aqueous solution of silane coupling agent KH550 with a concentration of 2 wt%. After soaking for 2 h, the mixture was filtered and dried to prepare a blend. Dissolve 1 kg of phenolic resin of type 2123 in 1.5 times its weight of ethanol, add the blend, impregnate at room temperature for 3 days, dry and pulverize.

[0032] Preparation Example 2: 0.05 kg of nickel nitrate and 0.1 kg of carbon nanotubes of type L-MWNT-4060 were dispersed in 0.6 kg of aqueous solution of silane coupling agent KH550 with a concentration of 4 wt%. After soaking for 2 h, the mixture was filtered and dried to prepare a blend. Dissolve 1 kg of phenolic resin of type 2123 in ethanol at twice its mass, add the mixture, impregnate at room temperature for 3 days, dry and pulverize.

[0033] Preparation Example 3: The difference from Preparation Example 1 is that nickel nitrate was not added.

[0034] Preparation Example 4: The difference from Preparation Example 1 is that no carbon nanotubes were added.

[0035] Examples of adhesive preparation 5-8 Preparation Example 5: 150g of molybdenum trioxide was added to 500g of deionized water, sonicated for 20min, and after being dispersed evenly, 276g of oxalic acid dihydrate was added, the temperature was raised to 80℃, and after stirring evenly, 270g of isopropanol and 1500g of polydopamine were added, sonicated for 30min, and then the temperature was raised to 180℃ and reacted for 24h. After centrifugation, vacuum drying, and grinding, the polydopamine was selected from Ruixi Biotechnology.

[0036] Preparation Example 6: 150g of molybdenum trioxide was added to 500g of deionized water, sonicated for 20min, and after being dispersed evenly, 276g of oxalic acid dihydrate was added, the temperature was raised to 80℃, and after stirring evenly, 250g of isopropanol and 1440g of polydopamine were added, sonicated for 30min, and then the temperature was raised to 180℃ and reacted for 24h. After centrifugation, vacuum drying, and grinding, the polydopamine was selected from Ruixi Biotechnology.

[0037] Preparation Example 7: The difference from Preparation Example 5 is that molybdenum trioxide was not added.

[0038] Preparation Example 8: The difference from Preparation Example 5 is that an equal amount of medium-temperature asphalt was used instead of polydopamine. The medium-temperature asphalt was selected from Hebei Zhengri Energy Technology Co., Ltd., model 001, with a softening point of 80-90℃.

[0039] Preparation example of needle-shaped coke A composed of mosaic structure Preparation Example 9: 150g of medium-temperature coal tar pitch was placed in a 250ml high-pressure reactor and heated to melt the pitch. The heating rate was 3℃ / min and the stirring rate was 180r / min. When the temperature reached 330℃, compressed air with a flow rate of 40l / h was introduced and the pressure was adjusted to 0.5MPa. The mixture was kept at this temperature for 8h to obtain oxidized modified pitch. The medium-temperature coal tar pitch was selected from Handan Jinghao Trading Co., Ltd., and the model was JH-006. Oxidized modified asphalt was placed in an autoclave and carbonized at a pressure of 0.5 MPa using nitrogen. The temperature was increased to 540°C at a rate of 3°C / min and maintained for 3 hours to obtain raw coke. Under nitrogen protection, the raw coke was calcined at 1400°C for 2 hours.

[0040] Preparation example of needle-shaped coke B composed of fibrous structure Preparation Example 10: 100g of naphthalene and 10g of anhydrous aluminum chloride were added to a reactor. The temperature was raised to 80℃ under nitrogen protection. After the naphthalene was completely melted, the mixture was stirred at 80℃ for 30min. The temperature was then raised to 260℃ and kept at a constant temperature for 4h. After the reaction was completed, stirring was stopped. After cooling, the black solid product was taken out, crushed, sieved, and thoroughly washed with 2mol / L dilute hydrochloric acid until no aluminum ions were found in the filtrate (detected with concentrated ammonia). The filtrate was then washed with deionized water until neutral and dried under vacuum at 50℃ to obtain a mesophase pitch with a softening point of 244.6℃, a QI content of 10.32%, and 100% wide-range streamline type. Mesophase pitch was pulverized to 200 mesh and heated from room temperature to 600℃ at a rate of 10℃ / min under nitrogen protection, with a nitrogen flow rate of 95ml / min, and calcined at 1MPa for 24h. Example

[0041] Example 1: A method for preparing a negative electrode material for a fast-charging lithium battery, comprising the following steps: S1. The graphite raw material is crushed, ground and classified to obtain aggregate with a particle size of 10 μm. The graphite raw material includes 60 wt% of needle coke A composed of an inlaid structure and 40 wt% of needle coke B composed of a fibrous structure. Needle coke A composed of an inlaid structure was prepared in Preparation Example 9 and needle coke B composed of a fibrous structure was prepared in Preparation Example 10. S2. Disperse 6 kg of tin chloride and 4 kg of hexamethylenetetramine in 15 kg of distilled water, heat to 180°C and keep at that temperature for 12 h, then cool to room temperature to obtain a blended solution. S3. Mix 20kg of aggregate with the blending liquid, freeze dry at -60℃ for 2 hours, mix with 2kg of binder, heat to 150℃, stir for 30 minutes, and press into shape with a pressure of 20MPa to obtain a sheet with a thickness of 1cm. The binder is medium-temperature asphalt, which is selected from Hebei Zhengri Energy Technology, model 001, with a softening point of 80-90℃. S4. After crushing and classifying the sheet material, calcining it in nitrogen at 750°C for 3 hours to obtain a composite material with a particle size of 8μm. S5. The composite material and carbon source are mixed at a mass ratio of 0.3:1, heated to 250℃, mixed and coated, and granulated at 1.7MPa for 1.5h to obtain the coated material. The carbon source is phenolic resin of type 2123. S6. The coating is carbonized in an inert atmosphere to obtain the negative electrode material. The inert gas is argon, the carbonization temperature is 1400℃, and the carbonization time is 3h.

[0042] Example 2: A method for preparing a fast-charging lithium battery anode material, comprising the following steps: S1. The graphite raw material is crushed, ground and classified to obtain aggregate with a particle size of 15 μm. The graphite raw material includes 30 wt% of needle coke A composed of an inlaid structure and 70 wt% of needle coke B composed of a fibrous structure. Needle coke A composed of an inlaid structure was prepared in Preparation Example 9 and needle coke B composed of a fibrous structure was prepared in Preparation Example 10. S2. Disperse 3 kg of tin chloride and 2 kg of hexamethylenetetramine in 10 kg of distilled water, heat to 200°C and keep at that temperature for 10 h, then cool to room temperature to obtain a blended solution. S3. Mix 10kg of aggregate with the blending liquid, freeze dry at -60℃ for 2 hours, mix with 1kg of binder, heat to 150℃, stir for 30 minutes, and press into shape with a pressure of 20MPa to obtain a sheet with a thickness of 1cm. The binder is medium-temperature asphalt, which is selected from Hebei Zhengri Energy Technology, model 001, with a softening point of 80-90℃. S4. After crushing and classifying the sheet material, calcine it in nitrogen at 800℃ for 2 hours to obtain a composite material with a particle size of 10μm. S5. The composite material and carbon source are mixed at a mass ratio of 0.1:1, heated to 200℃, mixed and coated, and granulated at 1.3MPa for 2 hours to obtain the coated material. The carbon source is phenolic resin of type 2123. S6. The coating is carbonized in an inert atmosphere to obtain the negative electrode material. The inert gas is argon, the carbonization temperature is 1200℃, and the carbonization time is 10h.

[0043] Example 3: A method for preparing a negative electrode material for fast-charging lithium batteries, the difference from Example 1 is that the graphite raw material is entirely composed of needle-shaped coke A with an embedded structure.

[0044] Example 4: A method for preparing a fast-charging lithium battery anode material, the difference from Example 1 is that the graphite raw material is entirely composed of needle-shaped coke B with a fibrous structure.

[0045] Example 5: A method for preparing a negative electrode material for fast-charging lithium batteries, which differs from Example 1 in that the graphite raw material is petroleum coke, selected from Anyang Jinyao Metallurgy, model JY-ZTJ-036.

[0046] Example 6: A method for preparing a fast-charging lithium battery anode material, which differs from Example 1 in that the carbon source is a modified phenolic resin, prepared in Example 1.

[0047] Example 7: A method for preparing a fast-charging lithium battery anode material, which differs from Example 1 in that the carbon source is a modified phenolic resin, prepared in Preparation Example 2.

[0048] Example 8: A method for preparing a fast-charging lithium battery anode material, which differs from Example 1 in that the carbon source is a modified phenolic resin, prepared in Preparation Example 3.

[0049] Example 9: A method for preparing a fast-charging lithium battery anode material, which differs from Example 1 in that the carbon source is a modified phenolic resin, prepared in Preparation Example 4.

[0050] Example 10: A method for preparing a fast-charging lithium battery anode material, the difference from Example 1 is that the binder is made from Preparation Example 5.

[0051] Example 11: A method for preparing a fast-charging lithium battery negative electrode material, the difference from Example 1 is that the binder is made from Preparation Example 6.

[0052] Example 12: A method for preparing a fast-charging lithium battery negative electrode material, the difference from Example 1 is that the binder is made from Preparation Example 7.

[0053] Example 13: A method for preparing a fast-charging lithium battery negative electrode material, the difference from Example 1 is that the binder is made from Preparation Example 8.

[0054] Example 14: A method for preparing a fast-charging lithium battery anode material, which differs from Example 1 in that the carbon source is a modified phenolic resin prepared in Example 1, and the binder is prepared in Example 5.

[0055] Example 15: A method for preparing a fast-charging lithium battery anode material, which differs from Example 14 in that the coating prepared in S5 undergoes the following pretreatment before carbonization: manganese chloride is dissolved in ethanol to prepare a 20wt% spraying solution, which is then uniformly sprayed onto the coating and dried. The mass ratio of the spraying solution to the coating is 0.12:1.

[0056] Comparative Example Comparative Example 1: A method for preparing a fast-charging lithium battery anode material, which differs from Example 1 in that hexamethylenetetramine is not added to the blend solution.

[0057] Comparative Example 2: A method for preparing a fast-charging lithium battery anode material, which differs from Example 1 in that no blending liquid is added, and the aggregate and binder are mixed and pressed into a sheet.

[0058] Comparative Example 3: A method for preparing a negative electrode material, comprising the following steps: 1) The needle-shaped raw coke is crushed, ground, and classified to obtain the first aggregate with a Dv50 of 8-9 μm; 2) The needle-shaped raw coke is calcined at low temperature in a rotary kiln at 1100-1400℃ for 1-5 hours, and then crushed, ground and classified to obtain a second aggregate with a Dv50 of 7-8 μm. 3) Stir and granulate the second aggregate with 9% asphalt by weight in a horizontal reactor. The reactor should be in an inert atmosphere. The heat treatment stirring speed is 24 Hz, the heating range is 25℃~600℃, and the heating rate is controlled at 2~3℃ / min. The holding time at 350℃ is 90min, and the holding time at 600℃ is 110min. 4) After sieving, the granulated product is mixed with the first aggregate in a ratio of 7:3 (i.e., containing 30% single particles) and then loaded into a graphite crucible for graphitization. The graphitization atmosphere is protected by inert gas, the graphitization temperature is 3000℃, and the graphitization time is 45h. 5) Add the graphitized product and liquid phase coating agent together at a weight ratio of 11% into the fusion machine, and add 3% of nano-conductive agent. Stir at 50 Hz and fuse for 6 min. 6) The above-mentioned fusion product is loaded into a graphite crucible and sent to a roller kiln for carbonization. The maximum carbonization temperature is 1150℃. After carbonization, it is directly screened and demagnetized to obtain composite graphite anode material.

[0059] Performance testing The negative electrode materials were prepared according to the methods in the examples and comparative examples, and the performance of the negative electrode materials was tested according to the following methods. The test results are recorded in Table 1.

[0060] 1. Specific surface area: The specific surface area of ​​the material was tested using the Quadrasorb SI-3MP fully automatic 3-station specific surface area and porosity analyzer from Micron Instruments, Inc., USA. 2. D50 median particle size: The D50 median particle size and particle size distribution range of the graphite anode material were tested using a laser particle size analyzer MS2000. 3. Electrochemical performance testing: Using lithium iron phosphate as the positive electrode and 1M-LiPF6+EC:DEC:DMC = 1:1:1 as the electrolyte, the areal density of the negative electrode was 70 g / m², and the compaction density was 1.20 g / cm³. 3 A 5Ah soft-pack battery was manufactured and its rate performance was tested. The battery was tested using the LAND battery testing system, and constant current charge and discharge tests were conducted at 0.1C with a voltage range of 0.001-1.5V. The test results are shown in Table 1.

[0061] Table 1

[0062] Based on the data in Table 1 and the preparation methods in Examples 1 and 2, it can be seen that the negative electrode material made by using a combination of needle coke A and needle coke B as graphite raw materials, phenolic resin as carbon source, and medium-temperature pitch as binder, and calcining and carbonizing, has a small specific surface area, high initial charge specific capacity, and large capacity retention rate after 100 cycles, and has good fast charging and cycle stability.

[0063] In Examples 3 and 4, needle coke A and needle coke B were used alone as graphite raw materials. Compared with Example 1, the anode materials prepared in Examples 3 and 4 had a lower initial charge specific capacity, a larger D50 median particle size, a smaller specific surface area, a lower density, and a smaller initial coulombic efficiency.

[0064] In Example 5, petroleum coke was used as graphite raw material. Tests showed that the specific surface area of ​​the prepared negative electrode material decreased, the particle size increased, the initial charge specific capacity decreased, and the fast charging effect was reduced.

[0065] Compared with Example 1, Examples 6 and 7 used modified phenolic resin as the carbon source. As shown in Table 1, the first charge specific capacity of the negative electrode materials prepared in Examples 6 and 7 was significantly increased, and the capacity retention rate after 100 cycles was increased, the cycle stability was enhanced, and the fast charging effect was further improved.

[0066] In Examples 8 and 9, the modified phenolic resins prepared in Preparation Example 3 and Preparation Example 4 were used, respectively. Compared with Preparation Example 1, Preparation Example 3 and Preparation Example 4 did not add nickel nitrate and carbon nanotubes, respectively. As shown in Table 1, the negative electrode materials prepared in Examples 8 and 9 had a lower 100-cycle capacity retention rate and a lower fast charging effect compared with Example 6.

[0067] Compared with Example 1, Examples 10 and 11 used polydopamine and molybdenum trioxide as raw materials to prepare binders. In Examples 10 and 11, binders prepared in Preparation Example 5 and Preparation Example 6 were used, respectively. As shown in Table 1, the negative electrode materials prepared in Examples 10 and 11 have increased specific capacity during the first charge and increased capacity retention rate after 100 cycles.

[0068] In Example 12, the binder prepared in Preparation Example 7 was used, in which molybdenum trioxide was not added. It was found that the first charging efficiency of the negative electrode material decreased and the 100-cycle capacity retention rate decreased. This indicates that adding molybdenum trioxide to polydopamine to make a binder can improve the first charging capacity and cycle stability of the negative electrode material.

[0069] In Example 13, the binder prepared in Preparation Example 8 was used, and medium-temperature pitch was used instead of polydopamine. After 100 cycles, the capacity retention rate of the negative electrode material prepared in Example 13 decreased significantly. The medium-temperature pitch caused the molybdenum carbide produced by molybdenum trioxide to agglomerate, which affected the structural stability after carbonization.

[0070] Compared with Example 1, Example 14 not only used the modified phenolic resin prepared in Example 1 as a carbon source, but also used the binder prepared in Example 5. As shown in Table 1, the negative electrode material prepared in Example 14 has a significantly increased first-charge specific capacity and enhanced cycle stability compared with Example 6 and Example 10.

[0071] Compared with Example 14, Example 15 further uses a solution containing manganese chloride to pretreat the coating, thereby increasing the initial charge specific capacity and improving the cycle stability of the negative electrode material obtained by carbonization treatment.

[0072] Compared with Example 1, no hexamethylenetetramine was added to the blend in Comparative Example 1, while no blend was added in Comparative Example 2. Table 1 shows that the specific capacity of the negative electrode material prepared in Comparative Example 1 decreased during the first charge, while the decrease was more significant in Comparative Example 2.

[0073] Comparative Example 3 is a negative electrode material provided in the prior art, which has a small specific surface area, large particle size, and a lower initial charge specific capacity than Example 1.

[0074] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A method for preparing a negative electrode material for a fast-charging lithium battery, characterized in that, Includes the following steps: Graphite raw materials are crushed, ground, and graded to obtain aggregates; Sturm chloride and hexamethylenetetramine are dispersed in distilled water, heated to 180-200℃ and kept at that temperature for 10-12 hours, then cooled to obtain a blend. The aggregate is mixed with the blend liquid, freeze-dried, mixed with the binder, and pressed into shape to obtain a sheet. The composite material is prepared by crushing and classifying the sheet material and then calcining it in nitrogen at 750-800℃. The composite material and carbon source are mixed and coated, then granulated to obtain the coated material; The coating was carbonized in an inert atmosphere to obtain the negative electrode material. The carbonization temperature was 1200-1400℃ and the carbonization time was 3-10h. The amounts of each raw material used in the negative electrode material are as follows: 10-20 parts aggregate, 3-6 parts tin chloride, 2-4 parts hexamethylenetetramine, 10-15 parts distilled water, 1-2 parts binder, and 0.1-0.2 parts carbon source.

2. The method for preparing the fast-charging lithium battery anode material according to claim 1, characterized in that: The carbon source is a modified phenolic resin, which comprises phenolic resin, nickel nitrate, and carbon nanotubes in a mass ratio of 1:0.05-0.1:0.1-0.

2.

3. The method for preparing the fast-charging lithium battery negative electrode material according to claim 2, characterized in that, The modified phenolic resin is prepared as follows: carbon nanotubes and nickel nitrate are mixed evenly and then added to a 2-4 wt% aqueous solution of silane coupling agent. After impregnation, the mixture is dried to form a blend. Dissolve the phenolic resin in a solvent with 1.5-2 times its weight, add the blend, impregnate, dry, and pulverize.

4. The method for preparing the fast-charging lithium battery anode material according to claim 1, characterized in that: The mass ratio of the composite material to the carbon source is 0.1:1 or 0.3:

1.

5. The method for preparing the fast-charging lithium battery negative electrode material according to claim 1, characterized in that, The composite material and carbon source are mixed and coated at a temperature of 200-250℃, a granulation pressure of 1.3-1.7MPa, and a granulation time of 1.5-2h.

6. The method for preparing the fast-charging lithium battery negative electrode material according to claim 1, characterized in that, The graphite raw material includes 30-60 wt% needle coke A composed of an inlaid structure and 40-70 wt% needle coke B composed of a fibrous structure.

7. The method for preparing the fast-charging lithium battery negative electrode material according to claim 1, characterized in that, The inert atmosphere is argon.

8. The method for preparing the fast-charging lithium battery negative electrode material according to claim 1, characterized in that, Before the coating is carbonized, it undergoes the following pretreatment: manganese chloride is dissolved in ethanol to prepare a spraying solution with a concentration of 10-20 wt%, which is then uniformly sprayed onto the coating and dried. The mass ratio of the spraying solution to the coating is 0.08-0.12:

1.

9. The method for preparing the fast-charging lithium battery anode material according to claim 1, characterized in that, The binder comprises polydopamine and molybdenum trioxide in a mass ratio of 9.6-10:1.

Citation Information

Patent Citations

  • Preparation method of modified lithium battery anode material

    CN105140483A

  • High-rate graphite negative electrode material and preparation method thereof

    CN116477615A